Türkiye’de kamu yatırımlarının 1980-90 döneminde gelişimi - Tezcek, F. Özlem (My University, 1999)
Bu çalismanin amaci: Türkiye'de 1980 sonrasinda sanayi sektörlerine yönelik olarak yapilan kamu yatirimlarindaki azalmanin, Türk sanayi sektöründe uzun dönemli durgunluk yarattigini ve ülkede sanayilesme sürecini devam ettirmek için devlet önderliginde sermaye-yogun yatirimlarin arttirilmasi gerektigini göstermektedir. 1980 yilinda IMF araciligiyla uygulanmasina karar verilen Yapisal Uyum Politikalari(YUP) Türk ekonomisinde devlet müdahalesinin azaltilmasina dayanir. YUP'un kabülündeki temel etken olarak ise, Türkiye'de 1960-80 döneminde uygulanan devletçi ve ithal ikamesine dayali ekonomi politikalarinin basarisizligi olarak gösterilir. Ancak böyle bir görüs Türk ekonomisinde sermayenin tarihsel birikim kaynagini gözardi etmekle beraber Türkiye'de yasanan sanayilesme sürecinin derinlikten uzak bir yorumunu içerir. Cumhuriyetin kurulusundan bu yana Türkiye'de devlet sanayilesmenin motoru olmustur. Kapitalizmin gelisim sürecinin gelismis ülkelerden farkli olarak yasandigi Türkiye'de, kapitalist sinif ekonomik gelisimi sürükleyen temel kesim olmaktan uzak kalmistir. Bu nedenle devlet 1980'lere kadar ekonomik gelisme çabalarinda aktif rol üslenmistir. Özellikle sanayi sektörlerine yaptigi sermaye-yogun yatirimlarla sanayilesme ve dolayisiyla ekonomik gelisimi saglayan devlet, 1980'den sonra izledigi bu politikadan vazgeçmis ve yatirimlarini alt-yapi ve konut yapimi sektörlerine kaydirmistir. Özellikle yeni yatirimlardan uzak kalan imalat sektöründe kapasite kullanim orani düsmüs ve üretim emek-yogun hale gelmistir. 1980 sonrasi uygulanan liberal ekonomi politikalari nedeniyle sanayi sektöründe ortaya çikan üretim düsüsleri ve ihracata yönelik imalat sektöründeki olumsuz anlamdaki yapisal degisim, Türkiye Cumhuriyeti'nin 57 yillik sanayilesmis ülkeler seviyesine ulasma amacini sekteye ugratirken ülkemizin gelismis ülkeler karsisindaki haklarini zedelemektedir. BÖLÜM 1:GELISME STRATEJISI OLARAK SANAYILESME Tanim olarak sanayilesme; üretimde emek ihtisaslasmasi; elektrik, mekanik ve teknoloji kullaniminin insan emeginin yerini almasi araciligiyla sekillenen isletme üretim organizasyonudur. Sanayi sektörü üretiminde temel olarak imalat, maden ve enerji sektörleri önem kazanir. Yapilan istatistiki arastirmalar göstermistir ki, 1970'lerden itibaren 1990'lara dogru dünya imalat katma degerinin bölüsümünde gelismis ülkelerin payi azalirken gelisen ülkelerin payi artmistir. Bu artisin büyük bir bölümü merkezi planli ülkelerle güney ve dogu Asya ülkelerine aitken, Türkiye'nin de içinde bulundugu Bati Asya ülkeleri bu artistan göreceli olarak az bir pay almaktadir. 1975'ten 1985'e kadar olan dönemde dünya imalat sanayi üretiminin gelismekte olan ülkeler arasindaki paylasimina gözatildiginda ise, süreç içinde özellikle Güney kore ile Tayvan'in payi artmistir. Türkiye'nin payi ise 1980'lerin basinda ülkenin dis borç krizi yüzünden azalirken 1985'li yillarda planli dönem süresince yaratilan teknik kapasitelerin kullaniminin artmasiyla yükselmistir. BÖLÜM 2: YATIRIMLAR YATIRIM: Belli bir dönem içinde üretilen ve ithal edilen mal ve hizmetlerin, özel sektör ve devlet sektörü tarafindan tüketilmeyen ve ihraç edilmeyen kismidir. Yatirim türleri sunlardir: -Brüt (Gayrisafi) yatirim: Bir ekonomide belli bir dönem içinde kullanilan reel sermayeye yapilan ilavelere brüt yatirim denir. -Net (Safi) yatirim: Belli bir dönem içinde brüt yatirimlardan asinma ve yipranma paylarinin çikarilmasiyla elde edilir. -Reel yatirim: Milli sermayeye bir dönem içinde makina, techizat ve stoklar seklinde eklenen üretim araçlarina yapilan yatirimlardir. -Mali yatirim: Herhangi bir kiymetli evragin alinmasiyla bireyi servetinde meydana gelen deger artislaridir. -Bagimsiz (otonom) yatirim: Gelirden bagimsiz olarak yapilan yatirimlardir. -Bagimli (uyarilmis) yatirim: Gelirdeki artisa bagimli olarak olusan yatirimlardir. -Kamu yatirimi: Devlet sermayesinin ekonomik kalkinma için gerekli alt-yapi yatirimlari, karlilik tasimayan sosyal içerikli yatirimlari ve tekel durumunun söz konusu oldugu alanlarda yapilmasi gereken yatirimlarinin finansmaninda kullanilmasidir. -Özel yatirim: Mütesebbisin kar elde etmek amaciyla sermayesiyle üretim araçlarini satinalmasi veya kiralamasidir. -Yabanci Sermaye yatirimi:Yabanci ülke mütesebbisinin kar elde etmek için kendi sermayesiyle bir baska ülkedeki üretim faktörlerini satinalmasi veya kiralamasidir. -Üst-yapi yatirimi: Tüketim, ara-mali, temel sinai ve tarimsal ürünleri üreten alanlara yapilan yatirimlardir. -Alt-yapi yatirimi: Mal ve hizmet üretimini saglayacak yol, köprü, baraj, liman v.b. dissallik özelligi tasiyan üretim birimlerinin insaa edilmesidir. BÖLÜM 3: KURAMSAL ÇERÇEVE -KLASIK IKTISAT KURAMINDA YATIRIM KAVRAMI: Klasik iktisatçilara göre gelirinden tasarruf edebilen tek sinif kapitalist siniftir. Kapitalist tasarrufunu ya diger üretim faktörlerini satinalarak ya da kiralayarak mal veya hizmet üretiminde kullanir ya da tasarrufunu faiz geliri karsiliginda kiralayarak rantiye adini alir. Sermaye birikimi ise tasarrufla artar, tüketimle azalir. Klasik iktisatçilar tüketimi en hos görülmeyen davranis olarak kabul etmislerdir. Klasiklere faiz haddinin para piyasasinda ve tasarruf ile yatirimin esitlendigi noktada olusur. Klasiklere göre para talebi yalnizca alisveris istegiyle gerçeklesirken, tüketim disi amaçlarla elde tutulan parayi ifade eden 'iddihar'gibi davranislar olumlu karsilanmamistir. -NEO-KLASIK IKTISAT KURAMINDA YATIRIM KAVRAMI: Neo-klasik iktisat kuraminin en önemli temsilcilerinden biri olan Wicksell ilk defa tabii faiz haddi (sermayenin marjinal verimi) ile piyasa faiz haddi arasindaki ayirimi yapmistir. Wicksell'e göre tasarruf üzerinde olusan yatirim miktari enflasyona neden olur. Yatirim üzerinde olusan tasarruf artisi ise tüketimin ertelenmesine neden olur. Wicksell faizin piyasa fiatinin fonlarin arz ve talebi tarafindan belirlendigini savunur. Wicksell fiatlarin yükseldigi duragan denge durumunu varsayar. Buna göre sermaye mallarinin cari fiatlari normalin üzerindeyken gelecekte inecek beklentisi vardir. Bu durumda yatirimin net kazancindaki azalmayla birlikte yatirimlar düser. Ödünç almanin maliyeti düserken üreticiler sermaye malinin fiatinin gelecekte daha da düsecegini umarak yatirimlarini ertelerler. Fisher'in miktar teorisine göre, paranin dolasim hizi ve islem hacmi degismez varsayilirsa para arzi ile fiatlar genel seviyesi arasindaki iliskiye dikkati çeker. -KEYNESYEN IKTISATTA YATIRIM KAVRAMI: Keynes'in faiz orani teorisine göre; faiz haddi Neo-klasik iktisatçilarin savunduklari tezdeki gibi otomatik olarak tasarruflari yatirima dönüstürmez. Çünkü paranin islem saikiyle talebi ile birlikte ihtiyat saikiyle de talebi söz konusudur. Faiz ancak yapilan ek bir yatirimin tüketimde azalma yarattigi tam istihdam durumunda bekleyisin ödülü olabilir. Diger durumlarda ise bu neo-klasik teori geçerli degildir. Keynes'in yatirim harcamalarinin belirlenmesi teorisine göre kapitalistin yeni bir sermaye mali satin almasini belirleyen temel faktörler: sermaye mallarinin maliyeti(i), beklenen T.L.kazanci ve faizin piyasa oranidir(r). Herhangi bir A yatirimi için r>i ise yatirim yapilir ve r=i oldugunda ise yatirim yapma istegi sona erer.Keynes ayrica yatirim talebi egrisinin belirlenmesinde bekleyilerin rolünü vurgular. Keynes'in faizin likitide tercihi teorisinde, nakit para tutmanin endiselerimizi yatistirdigi, faiz haddinin ise nakit para tutma isteginden ayrilisi tesvik ettigi belirtilir. Keynes'in likitide tuzagi teorisinde ise, likitide tuzaginin faiz oraninin çok düsük oldugu seviyelerdeki kullanilmayan likit kapasitelerden kaynaklandigi ve paranin islem ve ihtiyat istegiyle kullaniminin azaldigi bunalim dönemlerinde ortaya çiktigi savunulur. Ücret, fiat ve gelirin düstügü bu dönemlerde tasarruf sahipleri ellerindeki parayi spekülatif amaçlarla tutmayi çok düsük oranlarda faiz veren bankalara yatirmaya tercih ederler. BÖLÜM 4: SANAYILESME ALANINDA DÜNYADAN IKI ÖRNEK BREZILYA: 17. Yüzyilda ülke içinde üretilip ihraç edilen seker ve kahve nedeniyle Brezilya'da baslayan kolonilesme 1920'lere kadar devam etmistir. Kolonilesme Brezilya endüstrisine Avrupa isçi gelenegini tasimistir. 1929 Dünya Ekonomik Bunalimi etkisi ve Ikinci Dünya Savasi sonunda sorasinda daralan dünya talebi nedeniyle Brezilya 1940'larda ithal-ikameci ekonomi politikalari izlemistir. 1950'li yillarda devlet Brezilya'da sanayilesmeye büyük bir hiz verir. Bu dönemde de üretim tarzi ithal-ikameci bir özellik gösterir. Sanayilesmenin hizlanmasina ragmen devletin dis borçlari hizla artar. Ekonomik problemlerin büyümesiyle birlikte sosyal çalkantilar 1964'te bir askeri darbeye neden olur. 1970'lerin baslarinda ise Brezilya mucize dönemini yasar. Bu dönemdeki hizli ekonomik büyümenin temelinde devlet, yerli ve yabanci sermayenin yatirimlari yatar.Buna karsilik dis borçlar hizla artmaktadir. 1980'lere gelindiginde Brezilya'nin içinde bulundugu ekonomik kriz Türkiye'ninki ile birçok noktada benzerlik göstermektedir. IMF baskisiyla uygulanan liberal ekonomi politikalari nedeniyle devletin sanayi yatirimlari azalirken Brezilya'da sanayilesme sekteye ugramistir. GÜNEY KORE: Güney Kore 1910-40 yillari arasinda Kuzey Kore ile birlikte Japonya'nin egemenligi altinda bir sömürge ülkeydi. Bu dönemde Japon yönetimi Güney Kore'nin ekonomi ve politikasina kalici etkiler yapmistir. 1930'larda Japonya'nin sinir ötesi isgallere baslamasiyla birlikte Güney Kore'de silah ve makina fabrikalari kuruldu. 1930'larin sonlarinda Güney Kore disa açik bir ekonomiye sahipti. Ikinci Dünya Savasi sonunda Japonya'nin Kore üzerindeki hakimiyeti sona erdi ve Kore Güney ve Kuzey olmak üzere ikiye ayrildi. Bu dönemde yasanan Kore iç savasinin etkisiyle Güney Kore'de toprak reformu yapildi ve ülkeye 1960'larin sonlarina kadar sürecek ABD yardimlari gelmeye basladi. Güney Kore 1950'lerde ithal-ikameci ekonomi politikalari izleyerek ekonomik yapisini gelistirdi. Bu dönemde olusan dis ticaret açiklari ABD yardimlari sayesinde kapatilmistir. 1960'larin sonlarinda ABD yardimlari sona erdi ve ülke ihracata yönelik ekonomi politikalari izlemeye basladi. 1970'lerde Güney kore'de sermaye yogun sanayi sektörlerinde üretim yapilmasina agirlik verilirken isgücü egitimine önem verildi ve yeni teknolojilerin ülke içinde üretilmesi için çalismalara baslandi.1980'lerde ülkenin sermaye yogun mallar ihracatindaki üstünlügü artarken emek yogun mal ihracatindaki rekabet üstünlügü azaldi. Bu karsilik ar-ge faaliyetleri hizla artmaktadir. Güney Kore ve diger sanayilesen Asya ülkelerinde izlenen temel ekonomik stratejiler; içeride izlenen ithal-ikameci ve uluslararasi piyasalarda uygulanan ihracata yönelik ekonomi politikalarinin olusturdugu karma politikalardir. Bu politikalar vasitasiyla ekonomiyi kontrol altinda tutan devlet, her türlü olumsuz etkiden uzak otonom devlettir. BÖLÜM 5: TARIHSEL SÜREÇTE SERMAYE BIRIKIMI VE KAMU YATIRIMLARININ GELISIMI 1923-39 DÖNEMI : Cumhuriyetin ilk on yilinda uygulanan ekonomi politikalari 1923 Izmir Iktisat Kongresi'yle olustrulmustur.Bu dönemde özel girisimciligin canlandirilmasi ve sinai gelismenin saglanmasi için devletin gerekli alt-yapi yatirimlarini yapmasi öngörülmüstür. Bunun yanisira devlet ithalat ve ihracati kontrol altina almis ve demiryollari gibi bazi alanlarda kamulastirmalara gitmistir. Diger dönemlerle karsilastirildiginda bu dönem liberal ekonomi politikalarinin uygulandigi söylenebilir. 1929 Dünya Ekonomik Bunalimi'nin etkisiyle ülkede devletçi ekonomi politikalari uygulanmaya baslanir. Devletin yaptigi düzenlemelerle bu dönemde ticaret kosullari sanayi mallari lehine olarak gelisti.Kamu kesim kuruluslari vasitasiyla sanayideki sermaye birikimi hizla artti. Türkiye'de planlanan ve ilki basariyla gerçeklestirilen ilk iki kalkinma plani 1934 ve 1936'da hazirlandi. 1940-49 DÖNEMI: Bu dönemde Ikinci Dünya Savasi nedeniyle birçok Avrupa ülkesinde oldugu gibi Türkiye'de de devletçi ekonomi politikalari uygulandi. Savasin yarattigi olumsuz kosullarda devletçe olusturulan sermaye birikimi durdu. Türkiye'de ilk devalüasyon 1946 yilinda yapildi. Savas sonrasinda ABD'nin varolan kapitalist sistem içindeki hegemonyasini gerçekleyen Marshall Yardimlari basladi. ABD tarafindan Avrupa ülkelerine verilen bu yardimdan Türkiye de pay aldi. 1950-59 DÖNEMI: Bu dönemde Türkiye'de ilk defa çok partili seçimler yapildi ve on yil boyunca DP iktidari vasitasiyla liberal ekonomi politikalari uygulandi. Dönem boyunca özellikle kaynagi ABD'nin yardimlari seklinde karsilanan hizli bir ekonomik büyüme görülür. Uygulanan liberal politikalara ragmen devlet bu dönemde sanayi sektörlerine yogun olarak yatirim yapmis ve sanayilesmede ithal-ikameci politikalar uygulanmistir. Devletin sanayi sektöründeki faaliyetlere sagladigi kolayliklar nedeniyle yabanci sermayenin de ülkede faaliyet gösterdigi izleniyor fakat yabanci yatirimlar teknik yeniliklerden yoksundur. 1958'de yapilan ikinci devalüasyona ragmen dis borçlar dönemin sonlarina dogru ciddi bir sorun haline geliyor. Bu dönemde sanayilesmenin ilk asamasi olan tüketim mallari üretimi gerçeklestirilmistir. 1960-79 DÖNEMI: Bu dönemde Türkiye'de devlet önderliginde planli ekonomi politikalari uygulanir. Bu çerçevede dört tane kalkinma plani hayata geçirilir: B.B.Y.K.P.(1963-67), I.B.Y.K.P.(1968-72), Ü.B.Y.K.P.(1973-77), D.B.Y.K.P.(1978-83). Bu planlarin temel özelligi; planli bir ekonomik kalkinmanin benimsenmesi, kalkinmada sanayi sektörüne agirlik verilmesi, ulusal gelirin yilda yaklasik %7-8 oraninda artmasi, ekonomide disa bagimliligin en aza indirilmesi, sanayilesmenin ikinci asamasi olan ara ve yatirim mallari üretiminin gerçeklestirilmesi, v.s. dir. Bu dönemde devletin sanayi sektöründeki yatirmlari ve milli sermaye birikimi Cumhuriyet tarihinin en yüksek düzeyine ulasmistir ve Türkiye hizla sanayilesme yoluna girmistir. Bu dönemde saglanan hizli sanayilesme ve ekonomik büyümenin kaynagi ise özellikle 1962'de OECD ülkelerince kurulan Türkiye'ye Yardim Konsorsiyumudur. Bunun yanisira ABD yardimlari 1960'larin sonlarina kadar sürmüstür. IMF ise Türkiye'de uygulanan planli ekonomi politiklarina olumlu bakmadi. Dolayisiyla Türkiye IMF iliskileri 1970'lerdeki devalüasyona kadar olumsuzdu. 1970'de yapilan devalüasyonla Türkiye IMF'den 950 milyon dolarlik borç aldi. Türkiye 1974 petrol bunalimi adi altinda anilan sistem bunalimindan ülkeye giren isçi dövizleri sayesinde olumsuz yönde etkilenmedi.Bu kaynak 1970'lerin sonlarinda yokoldu. Fakat sistemin 1979'lardaki ikinci bunalimi Türkiye'yi askeri darbe ve ekonomi politikalarinin degisimine zorlayan ciddi bir dis borç krizi ile karsikarsiya birakti. BÖLÜM 6: 1980-90 DÖNEMINDE KAMU YATIRIMLARININ GELISIMI VE GENEL EKONOMIK YAPI Türkiye'nin 1970'lerin sonlarinda yasadigi dis borç krizi ve sonrasinda yasanan sosyal huzursuzluk ülkeyi en kisa zamanda bulunmasi gereken büyük oranli dis kaynak sorunuyla karsikarsiya birakti.Istenen borcu karsilamasi umulan IMF, bu borcun verilmesi karsiliginda Türkiye'de ekonomisinde köklü bir degisikligi sart kostu: Serbest piyasa ekonomisi ve uygulanacak liberal politikalarla devletin ekonomideki faaliyetlerinin daraltilmasi. Temelinde kapitalist sermayenin yeni pazarlar arayisinin oldugu bu yeni ekonomik politikalar, o dönemde IMF tarafindan pekçok azgelismis ülkeye tavsiye edilmistir. Yapisal Uyum Politikalari (YUP) olarak adlandirilan ekonomi paketinin 1980'de uygulamaya konmasiyla beraber Türk ekonomisinde sürekli devalüasyonlar, yüksek oranli faizler, yüksek oranli enflasyon, gelisme hizi duran sanayi sektörleri, sanayi ve özellikle imalat yerine konut yapimi ve ulastirma sektörlerinde artan kamu yatirimlari, artmaya devam eden kamu borçlari, ihracat sektörü ve rantiye kesimi lehine bozulan gelir dagilimi, teknik gelismelerin durdugu ve emek-yogun hale gelen imalat sektörü ve umulanin aksine artmayan reel yabanci sermaye yatirimlari gibi olumsuz gelismeler yasanmistir. SONUÇ Avrupa'da ortaya çikan ve gelisen kapitalizmin itici gücü kapitalist siniftir. Ancak azgelismis ülkelerde ve Türkiye'de kapitalizm çok farkli bir çizgide ilerlemektedir. Sermayenin uluslararasilasmasiyla kapitalizme ilk ciddi adimlarini atan azgelismis ülkelerde ekonomik gelisimin kaynagi kapitalist sinif degil devletin ekonomiye müdahalesinden ve ekonomideki düzenleyici rolünden kaynaklanir. Türkiye'de Cumhuriyet dönemi boyunca sanayilesme çizgisi incelendiginde; kapitalist sinifin henüz bu mekanizmayi tekbasina harekete geçirecek güç ve istege sahip olmadigi görülmektedir. Dolayisiyla devletin bu alanda ekonomiye müdahalesi ve düzenleyici tedbirleri gereklidir. Özellikle 1960'larin planli döneminde uygulanan sanayilesme politikalarinin basarisi gözönüne alinirsa Türk ekonomisinin bir yaniyla ithal-ikameci sanayilesme politikalari uygulamak yoluyla iç piyasanin, özel tesebbüsün ve genelde sanayi sektörünün gelistirilmesine ihtiyaci oldugu açikca görülür. Öte yandan 1980'li yillarda uygulana ihracata dönük ekonomi politikalariyla saglanan döviz gelirleri ve bu kaynagin Türk ekonomisi için gerekliligi dikkate alinirsa, ekonomide bir yaniyla ihracata yönelik ekonomi politikalarinin uygulanmasi olumlu olacaktir. Cumhuriyet tarihi boyunca her iki politikayi da uygulayan Türkiye, ithal-ikameci ve ihracat yönelik ekonomi politikalarini bir potada eritebilecek potansiyeldedir. Ancak dengeli bir kaynak dagilim ve piyasa düzenleme politikasinin uygulanmasini gerekli kilan bu karma ekonomi politikalari, herseyden önce tüm bu sartlari saglayabilecek ve çikar gruplarinin etkilerinden bagimsiz olarak faaliyet gösterebilecek güçlü ve otonom bir devlete ihtiyaç duyar. The aim of this study is to show that the decline of public investment in the industrial sectors has caused a long-term recession in the Turkish Industry since 1980. Therefore it is essential that the capital-intensive investments are implemented through the state's leadership in the industrial sectors in order to continue the industrialization process in Turkey. Faced with growing economic and political problems, the civilian government of the 1970s adopted a vigorous policy package on January 24, 1980 and planned a great restructuring of the economy with an emphasis on export-oriented growth policies. The IMF and the World Bank approved this decision. This policy package called 'The Stabilization and Structural Adjustment Program' (SSAP) was based on the principle of a reduced government intervention in the economy. It is thought that from 1970 to 1979, while the import-substitution growth policies were put into practice, the government spent most of public resources in the industrial sectors. Therefore the amount of domestic and foreign debt increased considerably. That is the main reason why the active state intervention and the import-substitution policies were replaced with SSAP. But it was not realized that the government investment in the industrial sectors had given rise to capital formation since 1923, which is the year of the establishment of the Turkish Republic. This amount of capital was the engine of industrialization in Turkey. At this point, one can ask the following question: 'What is the real cause of this huge amount of government debt at the end of the 1970s?' Is it because of the necessary public investment in the industrial sectors OR the non-planned expenditures of the governments in whole economy? Until the 1980s, the state took over the responsibility of investing in the industrial sectors, because of the private sector's lack of ability to invest in these sectors. Since 1980, the sectors, which the state invested, have changed dramatically. Therefore the growth of public investment in manufacturing and mining has been declining, although the growth of public investment in housing and infrastructure has been increasing. According to some economic indicators, the Turkish economy has been in long -term stagnation since 1980. The gross fixed capital formation has slowed down and the capacity utilization, which had rising through the public investments, has reached its technological optimum. Moreover there are no further investments to provide extra capacity. This put continual pressure on the industrial production. The Turkish manufacturing sector has transformed since 1980. After the capital formation declined in the sector, the manufacturing sector goods have been manufactured with labour-intensive methods. Since 1923, the principal objection of the Turkish Republic has been to transform itself into an industrial economy. First, Ataturk launched this goal because he wanted Turkish society to become a high-income one and producing goods with capital-intensive methods. As we approach the new millennium, not only Turkey but also other less-developed countries have not achieved the goal of industrialization. As a result of this, the developed world put an increasing economic and political pressure on less-developed countries. 2. AS A DEVELOPMENT STRATEGY: 'INDUSTRIALIZATION' In its broadest sense, the term industrialization indicates the organization of production in business enterprises, characterized by specialization and the division of labour. It involves in the application of technology and mechanical and electrical power to supplement and replace human labour. Industrialization is at the center of development. Since the industrial revolution in Britain, industrialization has been perhaps the single most profound change to the social and economic make up of societies. Industrialization is the central to increasing productive capacities and productivity. These processes are generally associated with growth in scale, specialization and mechanization. Three sectors are important in the industrial production: Manufacturing, mining and energy2. These are sectors where product diversification and technological innovation indicate the degree of industrialization in a country. The degree of industrialization is different between less developed and developed countries. The share of developed world in global MVA is 65.6% and the share of less developed world is 14.1% in 1988. Between less developed countries the highest share of global MVA belongs to Latin America and New Industrialized Countries (NIC). This share is 5.8% and 5.6% respectively. The share of other less developed countries (including Turkey) in global MVA is 2.1%. Over the same pried, the share of developed countries in global MVA fell from 73.7% in 1970 to an estimated 65.5% in 1988. This fall was largely the result of the rapid growth of the centrally planned economies and New Industrialized Asian Countries. During this period, the share of the centrally planned and New Industrialized Countries rose from 15.4%, 2.7% in 1970 to an estimated 20.4%, 5.6% in 1988 respectively. Despite the successful attempts in some less developed countries in general there is no significant increase in the degree of industrialization in the less developed world. On the other hand, a lot of survey clearly highlight that the experience of industrialization is uneven in the less developed world. The share of fifteen LDCs (Less Developed Countries) in global MVA is 77% in 1985. Over this period, Latin America (Brazil, Mexico, Argentina) and India are dominant the manufacturing production. Yet the share of this group fell 49.4% in 1975 to an estimated 41.6% in 1985. At the same time, there is a significant rise in the share of two highly successful East Asian Countries (Taiwan and South Korea) rose from 6.7% in 1975 to 11.8% in 1985. The share of Turkey is 4.3% in 1975 3.4% in 1980 and 4.3% in 1985. The fall in 1980 was the result of the debt crisis in 1980 and the reason for the rise in 1985 is the implementation of import substitution growth policies during the 1970s. 3. THEORICAL BASE a)INVESTMENT CONCEPT IN CLASSICAL ECONOMICS In classical economists point of view,the only social group which is able to save money is the capitalist class. A capitalist buys or rents manufacturing factors such as labour, machine or gets some interest profit with his money. Capital formation and economic development increase by saving and decrease by consuming. So classical economists do not approve consuming.In money market, there is the investment rate which occurs at point of the investment and saving are equal. The only reason for money demand is that people wants to buy goods. Classical economists did not notice that there is some money demand for speculation. b)INVESTMENT CONCEPT IN CLASSICAL ECONOMICS Wicksel, who is the important member of this economics separated money rate of interest and natural rate of investment(marjinal productivity of capital).According to Wicksell, if investment is more than saving in an economy, inflation occurs gradually.On the other side, if saving is more than investment, people postpone their consumption. c)INVESTMENT CONCEPT IN KEYNESIAN ECONOMICS Apart from neoclassic economists, Keynes do not think that savings converted into investment by the interest rate automatically.Because people do not only save their money for consuming. They also save the money for hoarding.If there is a full employment in an economy, peeple can obtain some interest rate profit by saving the money instead of consuming. Otherwise neoclassic analysis is not acceptable. According to Keynes, if the marjinal productivity of capital (i) is more than money rate of interest, a capitalist prefers to make an investment such as establishing a factory. If the marjinal productivity of capital is equal or less that the money rate of interest, a capitalist does not want to establish a factory and producing any goods or services. 4. ATTEMPTS AT INDUSTRIALIZATION OF TWO SELECTED COUNTRIES After Second World War, many colonized countries gained their independence. Together with them, the number of less-developed countries increased extremely. All these countries have some similar economic problems such as agriculture-intensive gross national production, market imperfections, low-income per head, a massive unemployment, inadequate saving and investment levels, slow progress of capital formation, lack of balance in income distribution, so on. Despite these similarities, each country has unique features of social, political, historical and economic institutions. They are very much unlike each other in many points. 'Being a colonized country' is the most distinctive character of some developing counties. These counties, for example: Chinese Province of Taiwan, South Korea, Hong-Kong, Singapore and Brazil are getting industrialized countries rapidly. On our point of view, 'the colonization process has a positive effect on the growth performance of economy in these countries. BRAZIL Brazil's industrial development started in the late 19th Century, on the back of colonization by Europe. In the 17th Century growing sugar consumption in Europe, turned out to be an increasing export demand for Brazil's sugar. Between 1887 and 1920, there were 1.7 million immigrants into Brazil in order to work in sugar and plantations or engineering workshops. Many of these immigrants came from Europe. Although the immigrants from Portugal and Spain were not generally industrial workers, they brought skills and traditions, which would strongly influence the course of Brazilian economic and political development. During the Great Depression, export earnings fell. Following a crisis in 1930, a new authoritarian government began to foster 'import-substitution growth policies' in order to promote the industrialization level. Domestic and foreign dept was increasing at the same era. In industry, the lion's share of output was in traditional sectors (such as food, textiles, wood and leather.) They were 70% of output in 1940. From 1920 to 1940, the share in industrial output of such industries as metal fabrication, machinery, chemicals and pharmaceuticals grew from 11% to 20.3%. These early developments formed the building blocks of Brazil's more rapid industrial development after the Second World War. In the 1950s, the State stimulated the industrialization process further more by implanting new industries and by developing the infrastructure. Consumer durable production expanded rapidly and participation of multinational firms increased. Production was still of the import substitution industrialization type. Rapid industrialization did not solve the balance of payments problems. While industry generated some new jobs, it could not absorb a huge wave of rural to urban migration. Increasing polarization over economic policy in the early 1960s led to a military coup in 1964. The period is between 1964 and 1974 called 'economic miracle'. In this period Brazilian economy grew extremely because of a partial shift from import substitution to export-oriented growth strategies. The direct state intervention grew in the economy and the integration increased with the world economy. Economic growth rates rose in GNP of 10% per year in between 1964-74. There was a considerable increase in investment levels which ere maintained by government, local and foreign businesses. In 1974, the Brazilian economy began to suffer from higher oil prices and the massive imports needed to sustain the industrialization of the economic miracle. The debt payments increased drastically. Labour activitizm was expanding and diffusing among the industrial workers. But the military restraint activities of trade unions and it put pressure on industrial wages. In the 1980s, the Brazil economy was dominated by the debt and inflation crisis. The economic management or government was very disappointing due to lack of any long term development planning. Instead, the government focused on some short term and crisis preventing policies (devaluation, price and wage freezes, etc). As a result, the real economic growth was in financial speculation. Industrially, the share of industrial output in GNP was declining dramatically. There was no coherent industrial policy to keep Brazil's industry going. As it is seen, the features of the economic crisis both in Brazil and Turkey in the 1980s show some similarities. The main reason for slowing down in industrialization speed in Brazil is the decline in growth of industrial investment. The governments held a large proportion in total investmentexpenditures until the 1980s. Since 1980, the government had nearly reduced dramatically its investment expenditure in the industrial sectors in order to provide economic liberalization. Further more, the foreign investment decreased due to lack of clarity in Brazil market. Financial investment is much more attractive to indigenous and foreign businesses than physical industrial investment. According to many surveys, the amount of investment in machinery and equipment tend to decrease in Brazil between 1978 and 1988. The decline in this kind of investment suppressed the manufacturing production. Similarly public investment tend to decline during the same period. The reason for this decline is the reduction of public investment in manufacturing. On the other hand, public investment in infrastructure and housing increased during this period. SOUTH KOREA Korea was colonized by Japan between 1910-45. The period of Japanese rule had a considerable impact on the economic and political structure and industrial development of South Korea7. Agricultural output in Korea rose by 74% between 1910 and 1940. The reason was that Japanese government supported the increase in agricultural income in order to get more taxes. Although agricultural output grew only as fast as the rate of population growth, industrial output grew more rapidly. This was particularly true in the 1930s as the Japanese war machine expanded with its invasion of Machuria (1931) and its southward expansion into the rest of China (1937). Koreans were forced from the land to work in Japanese-owned factories and by the end of the 1930s. In this period, manufacturing accounted for average 29% of total output, a figure that was high even for an advanced country. Most of this growth of industry, particularly heavy industry, was in what is now North Korea. Grain processing, textiles and some machinery developed in the more densely populated South. With the industrial development in Korea being closely linked with Japan, trade expanded. By the end of the 1930s, the Korean economy was an extremely 'open' one, where 50% of its output were traded. At the end of the Second World War, Japanese colonialism ended up with division of Korea into the communist North and the US backed South. The Korean War started in 1950. The reason for this was is quite controversial. Yet clearly it was an international war, a product of the Cold War between East and West. This war has two significant effects on South Korean's industrial development: * A land reform which took place in South Korea before and after war, * The immense increase in US aid to South Korea and the militarization of South Korean Society. In the 1950s, industrialization could be characterized as import-substitution. There is a rapid growth in South Korean manufacturing. Growth rate of manufacturing is over 18% a year. Cheabols, the large diversified business groups, which now dominate South Korean economy, were founded with the state support this period. During this era, the US aid provided the rapid industrial expansion with the foreign exchange. Between 1961 and 1970, was a period of spectacular growth. Economic growth was very fast and largely export-led. Actually it had to be because of the decline in the US aid. If South Korea intended to continue to growth, this source of foreign exchange had to be replaced by another. Foreign exchange was needed to import necessary capital equipment, raw materials and fuel. Consequently, Manufacture exports grew dramatically. Government actively promoted manufactured exports and encouraged companies to produce either protected domestic market (import substitution policy) or foreign market (export-oriented industrialization). At the same time business was supported and controlled by the government. In early 1970s, together with the fall in the exchange rates, real wages rose considerably. South Korea therefore was losing its international competitiveness in labour-intensive manufacturing goods exports. So the government took further step to develop heavy industries. South Korean industry was transforming rapidly. A brief economic crisis in 1980 was rapidly overcome. Favorable international exchange rates combine with investments overseas led to a greatly increased penetration of world markets. Since the 1980s, South Korean Company has relocated labour-intensive industries to lower cost countries such as Thailand, Malaysia, Indonesia, Philippines, etc. In South Korea the heavy industries have had come of age. In this period, even if economic liberalization demand increased, the government continued to direct the restructuring of industry and its investment. The capital formation level is significantly high in South Korea, due to three economic factors: * In colonization period, Japan provided large industrial investments with the country. * US aid continued until the 1960s. * After the 1960s, the amount of direct foreign investment has increased. As it is seen from some surveys, between 1980-90 the capital formation generally increased in South Korea except at the beginning of this period. There are two main reasons for this decline: The short-term debt crisis and the strict state regulation on the foreign investment profits. Many surveys shows that between 1980-90 the amount of total investment increased dramatically. The highest share belongs to machine and equipment investment and then infrastructure, non-residential building, housing respectively. Since the 1970s, NIC (New Industrialized Countries) have practiced the mixed growth policy. This policy consisted of import substitution growth policy, which protected the domestic market against the international competition, and outward-oriented export policy. In NIC, the state plays role in economic growth and the industrialization process. The main feature of this state is basically 'strength'8. Strong State is not static one. It changes over time in order to follow latest economic developments in the world markets. The mark of 'strong state' is the centralization of power, the right and ability to control social action and the regulation of economic activity. The strong state has an ability to reach into and directly interact with the population. The state has a power of negotiation with social interest groups. Consequently, the preferences, projects and policies of state elite generate independently of other power sources. State can not be reduced to a reflection of class forces and must be brought back in as an independent force and an actor in historical development. In Japan as well as South Korea, the state collects well-known statistics9. One very important role such statistic is to distinguish between two kinds of sectors. In the first one, there is a falling demand or temporary dislocation problems (for example, the need to invest in new machinery). In the second one there is fundamental structural problems of old technology, declining productivity, or incompetitive cost position. Especially Japan State has been able to identify these sectors, to recognize the difference between short run and long run difficulties, and to reallocate resources in a favor of industries with strong competition potential. In Japan, many companies are protected against international competitiveness for a certain period of time. At the end of this period, the protection is abolished and if this company did not improve its term of competitiveness in the world markets, the state punishes the company with extra economic responsibilities10. Many developing countries like Turkey practiced import-substitution growth strategies in their economies until the 1980s in order to improve industrial sector activities. Yet two consecutive petrol crises, which occurred in the 1970s, affected these economies badly. Because of the fall in export earnings, foreign debt increased dramatically many developing countries. Finally, some international donor organizations such as the IMF and the world bank recommended developing countries 'a magic medicine' called 'Structural Stabilization and Adjustment Policies'. Basically this policy packet consists of liberalization of economy and outward oriented growth strategies. In contrast to high level of economic development objectives, which was emphasized by this magic policy package in the 1980s, the results were disappointing in the 1990s. In this stage, I am going to start examining the unique case of the Turkish economy. This study will be in three sections: The role of Turkish state in the economy, 1923-69; Import substitution growth policies, 1970-79; Export-oriented growth policies, 1980-90. 5. THE HISTORICAL BACKGROUND OF CAPITAL FORMATION AND PUBLIC INVESTMENT IN TURKEY A. THE ROLE OF STATE IN THE ECONOMY, 1923-69. After Turkish Republic was established, state intervention occurred in economic activities. State intervention, so-called 'Etatism', was essentially a domestic and pragmatic response to the need felt by the Turkish leaders to promote the industrialization of the country in the face of unfavorable circumstances11. In the 1930s, state took the responsibility for investment in industrial sectors and set up some public companies. Between 1933 and the outbreak of World War Two, the government invested extensively in industrial factories. This investment was made in modern facilities, often without sufficient consideration for the availability of raw materials, fuel, labour, transport or markets. Yet Ataturk's purpose for establishing them was to create an industrial culture in the Turkish Republic. Moreover, a large number of plants were completed and industrial output expanded greatly. In the 1946 general elections, 'a multi-party's system' put into practice for the first time. Democratic Party (DP) won the election. Then it was realized that there was a corruption in the election. Four years later, in Turkey's first completely free and open election DP overcame difficulties and won this election too. When DP won the election, new government started seeking some growth policies, which voters would have been pleased with, in order to guarantee votes in the next election. Soon new policies came out. This scenario reveals the common characteristic of all Turkish governments. Since 1923, poverty and unemployment have been the most challenging problems that governments had to deal with. Therefore governments have been investing excessively in industrial sectors. It is thought that if new factories are established, more people can be employed in these factories and gradually the prosperity of Turkish public would rises. On the other hand, the concern for these governments is not in promoting 'industrial development' itself. Real concern of them is to keep their potential voters satisfied and ruling out Turkey as long as they could. This kind of concern brings out huge amount of non-planned industrial investment, based on short-term economic consideration and wasting of public resources (foolishly/ extremely). These populist economy policies, had two impacts in the Turkish economy: 1. The level of gross capital formation increased dramatically due to substantial amount of public investment, 2.Governments restricted on the long-term industrial development of the Turkish economy. In the 1950s, there was an 'expanding investment program' supported by the DP government. This program stimulated the private sector by general prosperity and proceeded with many industrial projects in transport, power, irrigation, mining and manufacturing. On the other hand, the increased money supply was generated by credit expansion, government deficits from public investment and grain subsidies. It reflected in increasingly unmanageable balance of payments' deficits and only later. Inflation was becoming a great threat to economic stability and development. Yet the government ignored the danger signals and warnings and took further step for new investment projects. Protests against the government and social dissatisfaction grew seriously. Finally, in 1960 a group of military officers took over the control of government. B. IMPORT-SUBSTITUTION GROWTH POLICIES,1960-79 After the 1960 coup, new constitution was established by Parliament. This new constitution declared that economic development would be undertaken in accordance with a plan. This decision was largely a reaction to the unplanned economic development, of in the 1950s. As a first step, The State Planning Organization (SPO) was established on September 1960. It played a central role in the government. The SPO provided the Turkish economy with suitable economic development policies, the coordination between the various ministries, agencies and private sector, the evolution of economic progress. The First (1963-67) and Second (1968-72) Five Year Development Plans was prepared under the leadership of the SPO. These plans brought greater discipline and consistency to the Turkish economic life and prevented the kind of economic disorder in the late 1950s. For the four years following the 1961 elections, Turkey was governed by a variety of weak coalition governments. The Justice Party (JP), which campaigned on a platform of more rapidly economic development, won the election in 1965. After 1965, economic development accelerated12. The average growth rate for 1966 and 1967 was 8%. This was mostly attributable to the higher level of investment. Unfortunately the JP was look like the DP. The JP therefore did not have any sharper insights into Turkey's problems and creative approaches to their solution. So regardless the JP continued to pursue populist growth policies. Except for the 1950-53 and 1970-73 periods, during which there were unfortunate attempts at foreign trade liberalization, trade and industrialization policies until 1980 were characterized by import-substituting industrialization. Industrial production shifted in the early 1960s from consumer durable to intermediate and capital goods. Public sector activity increased some capital-intensive branches such as petrochemicals, basic metals, fertilizers and paper. The rapid increase in manufacturing investment in the 1970s was promoted by the increase in export earnings, emigrant workers' remittances and the heavy short-term borrowing from international financial markets. The growth rate of manufacturing output was 7.5% per annum during 1950-80. Also public investment in manufacturing stimulated an enlargement and diversification (in/ of) industrial base. This was accompanied by a rise in the share of manufacturing in GDP from 1.4% in 1963 to 19.1% in 1979. As a result of this powerful growth performance Turkey rose to fifth in 1984 among the developing countries (behind China, Brazil, Mexico, India and South Korea)13. Despite this successful growth performance, a number of problems became increasingly clear in the second half of the 1970s and this model of industrialization could not be sustained by the economy. These problems can be shortly described under three headings: First, extensive and long-term protection created inefficient industrial structure14. Second, because of overvalued exchange rate and negative real rate of interest caused relative factor prices (to become) overvalued. Third, It was forced the level of industrialization to far away from available public resources. When we consider these problems comprehensively, the reason for these problems occurs clearly. Even if many economists agree with it, there was nothing wrong with the increase in public investment. Public investment was essential for the process of industrialization. Yet the matter was that the government mismanaged the economy and the governmental autonomy did not exist. Government's non-planned expenditure caused the decline in necessary public investment. Because of growing public sector deficits and import shortages, the rate of manufacturing investment fell from an average annual rate of 7.5% during 1963-77 to -10.2% during 1977-80. Similarly, the rate of growth of manufacturing output, which averaged 14.2% per annum during1973-77, averaged -0.6% during 1978-9015. C. EXPORT-ORIENTED GROWTH POLICIES, 1980-1990. In the late 1970s, the world petrol crisis struck Turkey as severely as many other developing countries. In addition, foreign debt, negative economic growth, high inflation, unemployment and series of shortages increased dramatically. Under these unfavorable circumstances, social and political unrest intensified and the government accepted a new policy packet, which was suggested by IMF and the World Bank. The name of this policy packet was SSAP, which campaigned for more Liberalization in the economy. The main headings of SSAP are in below: 1.'Liberalization of the Turkish economy' in order to reduce the huge amount of government debt. 2.'Crowding-out'. Decrease in public expenditure and promotion of private business. 3. Overvalued exchange rates and positive rate of interest. 4. Promotion of manufacturing exports. 5. Implementing new public investment in infrastructure. As a result of application of these policy tools in the economy, the state became liberalized at the expense of the industrialization process. Table 6 shows that the share of manufacturing in total public investment declined drastically. It was 23.8 % in 1973, 20.7% in 1978, 18.7% in 1984 and 4.5% in 1990. In contrast, the share of transportation was 26.4% in 1973 and rose (to) 34.1% in 1990. Also the resent experience does not support 'Crowding-out hypothesis' of Neo-classic approach16. There is no evidence that greater private sector activity may readily offset reduced government spending. In fact, there is 'a functional complementarity' between the public and private sectors in the Turkish economy. Also Table 6 shows that the share of manufacturing in total private sector investment decreased slightly during this period. It was 33.9% in 1973, fell to 27.5% in 1990. Two economic factors stimulated the deterioration of private investment in industrial sectors: First, the real rate of interest was increasing extremely so it was too expensive to get credit for industrialists. Second, the non-clarity in the domestic markets prevented all industrialists doing any further plan and investment for the future because there was a high risk of loss of his/ her capital. In Table 7, the investment rate of governments in manufacturing compared to that of housing. Although the rate in manufacturing increased in the 1970s, it declined in the 1980s. On the other hand, investment rate of government in housing generally increased in the 1980s. Also in the 1980s, the government invested in housing much more than (in) manufacturing. In the 1980s, the increase in the rate of interest stimulated saving, but caused deterioration in investment. Public resources therefore were not invested in production activities such as establishing new factories, instead they were invested in financial activities (government bonds, foreign exchange accounts, high-yield government securities, etc.). During the 1980s, the income distribution in Turkey showed a worsening picture17. Factor shares in national income changed considerably. There was regression in income distribution from popular sectors (agriculture, wages and salaries) to export profits, rents, and interest income. Factors share as per cent of national income for agriculture declined from 26.7% in 1980 to 13.2% in 1988. During the same period, the share of wages and salaries fell from 23.9% to 15.8%. On the other hand, the share of rents, profits and interest income increased from 49.5% in 1980 to 71% in 1988. Although the rate of total manufacturing investment declined in the 1980s, the production in the sector increased extremely18. The reasons for this increase are government support (export subsidies, tax credits etc.) and the decline in the rate of real wages in this sector. Since 1980, manufacturing is the most important component of total export earnings in Turkey. The government has given this sector an enormous support in order to increase the amount of foreign exchange. The productivity of industrial labour increased because of the high rate of labour supply in this sector. The implementation of export-oriented growth policies suppressed the domastic demand and the rate of real wage declined. During mid 1980s, the rate of nominal wages increased, but the rate of real wages was pressed by the high rate of inflation. As a result, the amount of export in manufacturing increased rapidly, due to relatively cheap price of manufacturing goods. On the other hand, the manufacturing sector was under pressure because of inadequate technologic equipment, which is essential in production19. The dilemma was that the public sector investment was reduced by SSAP, the private business was reluctant to invest in such productive sectors and it was difficult to import the necessary technologic equipment. Because of regular devaluation, the cost of foreign exchange was expensive. The import expenditure was not sustained anymore. In manufacturing sector production, technological development is very rapid. Capital-intensive techniques are implemented extensively in production. Furthermore there are some other less-developed countries, which export manufacturing goods at cheaper prices. So Turkey has to catch up with new technologies in order to keep its share of the world markets. In the manufacturing production, there is a need for both labor and technology. Unless the technology is provided sufficiently, the production will not increase in the long run. The short-term increase in the production is suppressed by the need of technology. The Turkish manufacturing sector experienced these bottlenecks since 1980. Table 9 and Table 10 show that the increase in the manufacturing production slowed down every two or three year. Since 1923, the state has improved the capital formation in the Turkish economy. Table 11 and Table 12 show that the fixed capital formation and the rate of capital-output increased continually. In addition, there is a significant rise in these two rates in the 1970s. During this period, the state implemented many capital-intensive industrial investments. The fixed capital formation and the rate of capital-out put are 22.6 million TL and 0.106199 respectively in 1948, they rise to 112029.8 million TL and 0.566299 respectively in 1977, fall to 44403.6 million TL and 0.164851 respectively in 1985. The foreign investments have no significant effect on the capital formation in the Turkish economy. In comparison to many developing countries, Turkey has never been colonized. The economic activities of developed countries were limited by the state in order to improve the domestic market and indigenous business. Since 1980, the approach of the governments to the way of economic growth has changed and the foreign investment has been supported by the governments. Table 13 shows that the amount of foreign investment is estimated in 338 million $, the share of foreign investment in manufacturing in the total foreign investment is 73.2% in 1980. The rate of capital inflow is 41.7% in 1980. Between 1981 and 1989, the foreign investment share of manufacturing in the total foreign investment falls continually. The share of foreign investment in manufacturing is 61.3% and the capital inflow into the Turkish economy is 50.2% in 1989. This shows that the half of the profits, which were made by foreign investment tents to go out of the Turkish economy. The reason for the 'Liberalization of the Turkish economy', which has been implemented in the economy since 1980, is to reduce state expenditure and the deficit in balance of payments20. Yet the result of this implementation is not satisfying at all. Table 14 shows that the share of government's investment expenditure in GNP is 12.4% during the period of 1978-79 and it rises to 13.5% in 1987. Similarly, the share of government total expenditure (consumption, investment and current transfer) in GNP is 25.8% in the period of 1978-79 and it rises to 34% in 1987. 6. OUTCOME At the end of the 1970s, there was a serious debt crisis in the Turkish economy. This huge amount of debt did not accumulate in five or ten year period. It had been expanding since the 1950s because of the inefficient state management of the economy. During that period, when the DP government implemented 'popular growth policies' into the Turkish economy, this debt started to accumulate and then the following governments carried out the similar policies. Yet many economists ignored this reality and they found an unrealistic explanation, which accused the state of investing far too much in the industrial sector. In 1979, the economic crisis worsened throughout the whole country rapidly and dangerously. The Turkish government requested help from the international donor communities in order to overcome this crisis. The remedy for this crisis was the SSAP, which were imposed on the Turkish economy by the IMF and the World Bank. The government obtained considerable amount of foreign exchange from them. This foreign exchange provided the Turkish economy with a short-term relaxation. On the other hand, this relaxation did not resolve the real problem. In addition, the criticism to the implementation of SSAP was suppressed by the military government. With appliance (to) SSAP the Turkish governments changed their traditional attitude to the economic growth. They started implementing some short-term crisis preventing economy policies instead of 'the growth policies on the industrialization base '. Outward oriented new policies reduced domestic demand and aimed at producing for international markets. In the industrial sectors, SSAP supported the export of manufacturing sector. The share of manufacturing export in total export is 28.8% in 1980 and it rises to 72.1% in 1990. Especially export of the textile and clothing sectors increased drastically. On the other hand, the public and private investment declined in the industrial sectors rapidly. The state investment shifted from the industrial sectors to infrastructure. Moreover, the private business invested in financial markets in order to get quick and the highest profit. Contrary to expectation, foreign capitalist did not find industrial sectors attractive enough for investment. Instead like the indigenous capitalist class, the foreign capitalist invested in financial markets too. Consequently, the public resources were destroyed by both foreign and indigenous capitalists. Since 1980, the manufacturing sector is in real danger. From then on, the goods are manufactured with obsolete technological methods. There are no further capital investment in the sector. In addition, attention was given too much the textile and clothing sectors. It is necessary to diversify the risk of profitable sectors in order to keep the competitiveness of these sectors in the world markets. There are also some economic indicators, which reveal a serious economic recession since 1980: the high rate of government debt, a chronic inflation, the high rate of interest and the decline in the industrial investment. Because of the neglect in the industrial sector for two decades, there is an urgent need for an active industrialization strategy. This new strategy must accelerate the investment in export activities as well as efficient import-substitution. The state is expected to play a dual role under this strategy: First, the government provides the domestic suppliers with the suitable price and trade policies. Second, the state introduces directly new enterprises in capital- and skill-intensive lines of activity. Furthermore, lessons can be drawn from NIC's experiences. For instance, the Turkish policy makers can learn how to invest in upgrading and diversifying the industrial structure. It is necessary to concentrate on prior sectors under state guidance and emphasis on the technological capabilities through investment in education and research. In addition, all these activities should be adopted carefully in the structure of the Turkish economy. Turkey and many other less developed countries experienced two alternative economic growth strategies. While ISI is highly effective in accelerating the industrialization process, the EOI is more effective in the penetration of world markets. The ISI and EOI can be complementary. As a result, a new industrial growth policy needs to combine these two strategies in the industrial base through the active state participation.
Keywords: Ekonomi; Finansman ekonomisi; KAMU YATIRIMLARI; Yatırım; YATIRIM; Yurt içi yatırım